PENGEMBANGAN MULTIMEDIA INTERAKTIF SILAT PEDANG UNTUK PEMBELAJARAN SENI TARI PADA SISWA SEKOLAH DASAR - Dwi Anggraini (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2014)
Abstract: The study was intended to produce a Silat Pedang interactive multimedia to teach dancing course at elementary schools. The research model used was ADDIE (Analysis, Design, Development, Implementation, and Evaluation) for the elementary school level. The data was obtained from observation, interview, documentation study, and questionnaires which were given to the students and the teachers of the fourth grade at Tunas Unggul Olus National School. The results of the study suggested that Silat Pedang interactive multimedia could improve the effectiveness of the teaching and learning outcome because it fulfilled the requirements of relevancy, convenience, attractiveness, and expediency.Keywords: interactive multimedia, ADDIE model, silat pedangAbstrak: Penelitian ini bertujuan menghasilkan produk multimedia interaktif silat pedang untuk pembelajaran seni tari di SD. Model penelitian menggunakan model ADDIE (Analysis, Design,Development, Implementation and Evaluation) pada tingkat Sekolah Dasar. Data diperoleh dari hasil observasi, wawancara, studi dokumentasi dan kuesioner yang diberikan kepada siswa dan guru kelas 4 Sekolah Olus Nasional Tunas Unggul. Hasil penelitian menunjukkan bahwa multimedia interaktif silat pedang dapat meningkatkan efektivitas pencapaian tujuan pembelajaran karena memenuhi syarat-syarat kesesuaian atau relevansi, kemudahan, kemenarikan, dan kemanfaatan.Kata kunci: multimedia interaktif, model ADDIE, silat pedang.